Parental Education and Child Health: Evidence from a Schooling Reform - Maarten Lindeboom; Ana Llena Nozal; Bas van der Klaauw (Tinbergen Institute, 2006)
This paper investigates the impact of parental education on child health outcomes. To identify the causal effect we explore exogenous variation in parental education induced by a schooling reform in 1947, which raised the minimum school leaving age in the UK. Findings based on data from the National Child Development Study suggest that postponing the school leaving age by one year had little effect on the health of their offspring. Schooling did however improve economic opportunities by reducing financial difficulties among households. We conclude from this that the effects of parental income on child health are at most modest.
Keywords: I12; I28; 330; returns to education; intergenerational mobility; health; regression-discontinuity